2013
DOI: 10.2196/jmir.2356
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences With Full Electronic Access to Health Records and Clinical Notes Through the My HealtheVet Personal Health Record Pilot: Qualitative Study

Abstract: BackgroundFull sharing of the electronic health record with patients has been identified as an important opportunity to engage patients in their health and health care. The My HealtheVet Pilot, the initial personal health record of the US Department of Veterans Affairs, allowed patients and their delegates to view and download content in their electronic health record, including clinical notes, laboratory tests, and imaging reports.ObjectiveA qualitative study with purposeful sampling sought to examine patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
189
2
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(210 citation statements)
references
References 23 publications
(20 reference statements)
7
189
2
10
Order By: Relevance
“…27 Several EHR developers have created patient portals, such as Epic's MyChart or the Veterans Health Administration's My HealtheVet, to meliorate communication with patients. 28,29 Both systems have functions that allow patients to review their own test results; more detailed nuances including the types of tests available for review, when results are posted (e.g., immediately upon completion of testing or only after provider review and approval) can often by controlled by individual providers or computer system administrators. Little attention has been given to whether such portals are viewed favorably by patients or to precisely which tests or results might not be suitable for communication via portals.…”
Section: Discussionmentioning
confidence: 99%
“…27 Several EHR developers have created patient portals, such as Epic's MyChart or the Veterans Health Administration's My HealtheVet, to meliorate communication with patients. 28,29 Both systems have functions that allow patients to review their own test results; more detailed nuances including the types of tests available for review, when results are posted (e.g., immediately upon completion of testing or only after provider review and approval) can often by controlled by individual providers or computer system administrators. Little attention has been given to whether such portals are viewed favorably by patients or to precisely which tests or results might not be suitable for communication via portals.…”
Section: Discussionmentioning
confidence: 99%
“…Patient portals and direct access to visit notes can support the information-sharing and deliberation steps of SDM by engaging patients in their own care [69][70][71] and increasing clinicians' responsiveness to patients' preferences and needs. 72 Well-designed patient portals can function similar to decision aids; patients who use patient portals to reflect on their health status and care before a visit may be better able to process risks and benefits of a health decision.…”
Section: Ehr: Patient Portals and Shared Visit Notesmentioning
confidence: 99%
“…[76][77][78][79][80] Some patients may have concerns about trust and privacy that could be worsened by real or perceived stigma in visit notes. 71,74,81 For example, in a Veterans Affairs shared notes study, some patients took issue with the way their clinicians described them. 71 Clinicians can help mitigate concerns by purposely writing and speaking with cultural sensitivity; this includes asking racial/ethnic minority LGBT patients which terms they prefer to describe their identities (Table 2).…”
Section: Ehr: Patient Portals and Shared Visit Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…After a successful pilot in which researchers found that "Viewing their records appears to empower patients and enhance their contributions to care" (Woods et al, 2013), VA in 2013 made clinical notes available through MyHealtheVet, including outpatient primary care and specialty visit notes, discharge summaries, and emergency department visit notes (VA, 2013a). A survey of early adopters found that a majority of the users of VA's version, called VA Notes, agreed that "accessing their notes will help them to do a better job of taking medications as prescribed (80.1 per cent) and be better prepared for clinic visits (88.6 per cent)" (Nazi et al, 2014).…”
Section: Myhealthevetmentioning
confidence: 99%